Gestión administrativa y financiera y su influencia en la rentabilidad del Centro Comercial “Su Economía” en el cantón Valencia, provincia de Los Ríos, Año 2020 - Mendoza Arias, Andrea Abigail (2021)
The general objective of this research was to analyze the administrative and financial management applied by the "Su Economía" Shopping Center, focusing on the management of planning, organization, direction and control processes, developed to take advantage of human, technical, and material resources , which affect the commercial profitability of the company; In addition to determining the incidence of administrative and financial management on the profitability of the Shopping Center by contrasting variables, for this, the census directed at the company's staff was applied, and the owner was interviewed; The methodology was based on descriptive, bibliographic, field research types, while the methods used were analytical-synthetic, inductive-deductive. Through the application of research instruments it was possible to identify that in the Su Economics did not have a defined administrative and financial management model, because relevant deficiencies were identified in the planning processes. The contracting of the variables using the chi-square calculation reflected X2 = 5.06, thereby accepting the positive hypothesis that stated that administrative management had an impact on the profitability of the company. Given the results obtained, it was considered suitable, he suggested a model according to the criteria of Henry Fayol that was based on the four administrative stages through indicators that reflected that only 50% of the members had knowledge of the mission and vision of the company It was also known that 45% consider that they do not participate in decision-making. While in reference to the level of efficiency, it stood at 50%, reflecting that there was no satisfactory fulfillment of the goals, due to unforeseen events. In the financial aspect, it was possible to establish a level of 1.04 for the current ratio, 0.68 for the acid test, while the level of indebtedness stood at 0.13